1999
DOI: 10.1021/bi991545c
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Cytochrome c Oxidase-Driven H+-Coupled Phosphate Transport Catalyzed by the Saccharomyces cerevisiae Pho84 Permease in Coreconstituted Vesicles

Abstract: Studies of cytochrome c oxidase-driven H+-coupled phosphate transport catalyzed by the Saccharomyces cerevisiae Pho84 permease in coreconstituted vesicles Fristedt, U.; van der Rest, M.E.; Poolman, Berend; Konings, W.N; Persson, B.L. IMPORTANT NOTE: You are advised to consult the publisher's version (publisher's PDF) if you wish to cite from it. Please check the document version below. Document VersionPublisher's PDF, also known as Version of record Publication date: 1999Link to publication in University of Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Recombinant Pho84p was found to require the presence of metal ions such as manganese and cobalt for phosphate transport, and a MeHPO 4 metal-phosphate complex was the proposed substrate. Not all metal phosphate complexes are good substrates for Pho84p, as the addition of magnesium was shown to actually have an inhibitory effect on phosphate transport with recombinant Pho84p (47). Consistent with this, we found an inhibitory effect of magnesium on the Pho84p-dependent uptake of manganese in vivo (data not shown).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Recombinant Pho84p was found to require the presence of metal ions such as manganese and cobalt for phosphate transport, and a MeHPO 4 metal-phosphate complex was the proposed substrate. Not all metal phosphate complexes are good substrates for Pho84p, as the addition of magnesium was shown to actually have an inhibitory effect on phosphate transport with recombinant Pho84p (47). Consistent with this, we found an inhibitory effect of magnesium on the Pho84p-dependent uptake of manganese in vivo (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…Evidence for such a transport mechanism has come from studies of recombinant Pho84p in reconstituted proteoliposomes (47). Recombinant Pho84p was found to require the presence of metal ions such as manganese and cobalt for phosphate transport, and a MeHPO 4 metal-phosphate complex was the proposed substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport substrate of Pho84 is a complex of phosphate anion and divalent metal cation (Fristedt et al 1999). In standard laboratory media, magnesium concentrations are relatively high, and the substrate for Pho84 is likely a MgHPO 4 complex.…”
Section: Phosphate-dependent Manganese Transportmentioning
confidence: 99%
“…Using reconstituted proteoliposomes, Fristedt and colleagues have shown that recombinant Pho84p can transport metal-phosphate (MeHPO 4 ) complexes, with manganesephosphate being a particularly good substrate (21). It is therefore conceivable that when yeast cells are exposed to very high levels of manganese, the manganese-phosphate complexes that form in the environment are readily taken up via the Pho84p transporter (Fig.…”
Section: When Manganese Levels Become Toxic: Bringing the Metal In Anmentioning
confidence: 99%